UMP to host SUKUM 2018 - Siti Sarah, Mohamad Rajimi (2017)
Universiti Malaysia Pahang (UMP) will be hosted SUKUM 2018 next year. UMP Registrar, Abd. Hamid Majid, received the SUKUM 2018 tournament flag from Universiti Pendidikan Sultan Idris (UPSI) Vice Chancellor, Prof. Dato' Dr. Mohammad Shatar Sabran.